Four score for predicting early mortality in patients with closed traumatic brain injury in the emergency department of Antioquia-Colombia (2022)
ABSTRACT: OBJECTIVE: To evaluate the predictive performance of the Full Outline of UnResponsiveness (FOUR) score for in-hospital mortality in patients with moderate and severe traumatic brain injury (TBI) treated in emergency departments in Antioquia-Colombia. METHODS: Prospective cohort study in subjects with moderate and severe TBI treated at the emergency departments of three hospitals between June 2021 and February 2022. The discrimination performance of the FOUR score and the Glasgow Coma Scale (GCS) was determined by calculating the C index and the AUC-ROC, and the calibration using a likelihood test. The association between the different values of the scales and in-hospital mortality was estimated through a multivariate logistic regression model. RESULTS: 101 cases were analyzed, 61.3% were classified as severe and 38.7% as moderate. Overall mortality was 28.71%, 14.50%, and 38.70% for moderate and severe TBI respectively. The AUC-ROC for mortality of the FOUR score was 0.70 (95% CI 0.58-0.81), and 0.75 (95% CI 0.64-0.85) for the GCS. When adjusting for variables of interest, AUC-ROC for FOUR of 0.916 (95% CI 0.84-0.98) and 0.916 (0.843-0.989) for GCS. Calibration for the FOUR score was adequate (likelihood test with a p-value of 0.0003). The OR for in-hospital death was 3.4; (95% CI 1.40-8.75) and 4.7 (95% CI 1.05-20.93) in the crude and multivariate analysis, respectively, when the score was 8 or less. CONCLUSIONS: The FOUR score predicts in-hospital mortality in a similar way to the GCS in patients with moderate and severe TBI.